2018
DOI: 10.1002/jgh3.12106
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delayed hemorrhage after colonoscopic postpolypectomy: Polyp size and operative modality

Abstract: Background and Aim Delayed postpolypectomy hemorrhage is relatively common, with occasional extensive blood loss, endangering life. This study aimed to determine the factors associated with postoperative hemorrhage. Methods The study was a retrospective cohort study of patients hospitalized for colonoscopic polypectomy at the Department of Gastroenterology and Hepatology, Tenth People's Hospital of Tongji University, China, between January and December 2015. Data on gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…After removal of duplicates, 895 were excluded based on study title and abstract, and 212 underwent full text review, of which 21 articles comparing ESD with EMR in resection of colorectal polyps were subsequently included in the meta-analysis (Figure 1 )[ 8 - 16 , 26 - 37 ]. In total, 12 originated from Japan[ 26 - 37 ], five from European[ 10 - 13 , 16 ], three from South Korea[ 8 , 9 , 14 ] and one from China[ 15 ]. Of the 21 studies, there were 17 retrospective cohort studies, two prospective cohort studies and two retrospective case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplicates, 895 were excluded based on study title and abstract, and 212 underwent full text review, of which 21 articles comparing ESD with EMR in resection of colorectal polyps were subsequently included in the meta-analysis (Figure 1 )[ 8 - 16 , 26 - 37 ]. In total, 12 originated from Japan[ 26 - 37 ], five from European[ 10 - 13 , 16 ], three from South Korea[ 8 , 9 , 14 ] and one from China[ 15 ]. Of the 21 studies, there were 17 retrospective cohort studies, two prospective cohort studies and two retrospective case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Its incidence lies between 0.3 -3.8 % of patients. Higher rates of delayed bleeding are associated with the removal of larger polyps (> 20 mm) [4,5,6,7,8,9]; furthermore, in patients receiving anticoagulation therapy or bridging with low molecular weight heparin, the incidence of delayed bleeding may increase to 11 % [10,11]. A limitation in all these studies was the rarity of delayed bleeding, resulting in low statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…1). [9][10][11][12][13][14][15][16][17][27][28][29][30][31][32][33][34][35][36][37][38] In total, 12 originated from Japan [27][28][29][30][31][32][33][34][35][36][37][38] , ve from European [11][12][13][14]17 , three from South Korea 9, 10, 15 and one from China 16 . Of the 21 studies, there were 17 retrospective cohort studies, two prospective cohort studies and two retrospective case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Previous meta-analyses and systematic reviews comparing ESD with EMR mainly focused on data reported from Asian countries with limited data coming from outside of Japan, without controlling for confounders or lesions <20mm. 7,8 Since then, numerous studies comparing between ESD and EMR have been reported from the West and other countries [9][10][11][12][13][14][15][16][17] We sought to perform an expanded meta-analysis to include lesions ≤20mm, and incorporate regression analysis to control for confounders.…”
Section: Introductionmentioning
confidence: 99%